The effect of rotenone crude extract from derris elliptica on the larvicidal activity (mortality) of mosquito - Zubairi, Saiful Irwan; Sarmidi, M. R.; Aziz, R. A.; Latip, R.; Said, J. (2004)
Rotenone is a bio-active compound extracted from Derris elliptica (Tuba). It has long been used as biopesticide, which is more environmental friendly. Recently, new processing methods have been published on the extraction and usage of rotenone. The objective of this paper is to obtain the effectiveness of Derris plant crude extract against mosquito larvae. Rotenone crude extract was extracted using Normal Soaking Extraction (NSE) method. Two different solvent ratios were used to extract rotenone which is: (A) Methyl chloride: methanol (1:1) and (B) Methyl chloride: methanol (1:9). One part of both crude extracts using solvent ratios A and B were concentrated further using the rotary evaporator at 40 0C and under 800 mbar vacuum pressures. All the samples (normal and concentrated) were subjected to larvicidal activity testing using mosquito larvae. The samples were diluted to 5 different concentrations (0.01 mg/ml, 0.02 mg/ml, 0.03 mg/ml, 0.04 mg/ml and 0.05 mg/ml) for the biological activity treatment (LC50). Six larvae of Aedes aegypti were used to test each samples. The study found that concentrated crude extract (B) using solvent ratio (1:1) gave optimum mortality of mosquito larvae of 83.33 % at 0.05 mg/ml after 5 hours post treatment.